(3GdBKGQ GdGbJUGOjI ddJehjd HGdYLR ef efXhQ Gdabg GdESdGei hGdEbJUGOi GdhVYi (B/s - (3GdeZQHj, GHQGgje eJhdi GHQGgje MSfs ((3GdEScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2010)
(3GdJYQja HeaQOGJ GdHMK,GdJehjd HGdYLR aj GdGbJUGO GdhVYi hGdGbJUGO GdGSdGei,GdMGLI Gdi GdJehjd HGdYLR aj GdGbJUGO GdhVYi hGdGbJUGO GdGSdGei,eUGOQ GdJehjd HGdYLR aj GdGbJUGO GdhVYi hGdGbJUGO GdGSdGei,BKGQ GdJehjd HGdYLR,GdJKHjJ ef aGYdjI GdJehjd HGdYLR hHOGFdg(B.s
(3bGFeI GdeQGLY U(B.459s
Keywords: (3GdEbJUGO GdESdGejs; (3GdJehjds; (3GdJehjd(B- (3Gdabg GdESdGejs